2010
DOI: 10.1111/j.1399-3062.2010.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 6-related pure red cell aplasia, secondary graft failure, and clinical severe immune suppression after allogeneic hematopoietic cell transplantation successfully treated with foscarnet

Abstract: Human herpesvirus 6 (HHV-6) is frequently detected after allogeneic hematopoietic cell transplantation (allo-HCT); however, the clinical interpretation of HHV-6 viremia in a transplant patient is challenging as it may signify asymptomatic reactivation, chromosomal integration of the virus genome in the donor or recipient with no clinical significance, or severe HHV-6 disease. Here we present a case of HHV-6 disease after allo-HCT presenting as pure red cell aplasia, secondary graft failure, and severe immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…23,29,33,34 Moreover, delayed complications with HHV-6 have also been described including pure red cell aplasia and secondary graft failure. 35 In our examination of the tissue-positive viremic group, there was a wide spectrum of end organs involved. In addition to the central nervous system, lungs, and bone marrow, HHV-6 was found in pericardial fluid, gallbladder, sinuses, and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 81%
“…23,29,33,34 Moreover, delayed complications with HHV-6 have also been described including pure red cell aplasia and secondary graft failure. 35 In our examination of the tissue-positive viremic group, there was a wide spectrum of end organs involved. In addition to the central nervous system, lungs, and bone marrow, HHV-6 was found in pericardial fluid, gallbladder, sinuses, and the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 81%
“…15 In the bone marrow transplant literature, HHV-6 has not only been associated with marrow suppression, 16 but with graft failure as well. 3 In these cases, however, the patients experienced severe bicytopenia or pancytopenia, not PRCA.…”
Section: Pure Red Cell Aplasia With Isolated Human Herpes Virus 6 Infmentioning
confidence: 95%
“…Infection in immunocompromised hosts can be more severe, frequently causing end organ damage. 3 Given its pathogenic effects on bone marrow, a causative role of HHV-6 in TEC has been explored with conflicting results. 4,5 We describe a 2-year-old female child status post cardiac transplant on immunosuppression presenting with severe anemia who was subsequently found to have HHV-6 infection isolated to the bone marrow.…”
Section: Pure Red Cell Aplasia With Isolated Human Herpes Virus 6 Infmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in one study, when prospective monitoring of HHV‐6 infections was performed following bone marrow transplantation, occurrence of anemia was significantly more frequent in HHV6‐infected transplanted recipients than in uninfected ones [24]. Recently, Lagadinou et al [25] reported a rather convincing case of HHV‐6 infection associated with PRCA also after allogenic hematopoietic cell transplantation. In this case, strikingly high HHV‐6 viremia was detected in the allotransplanted recipient concomitantly with PRCA and, when antiviral therapy was instituted, blood content in hemoglobin returned within normal limits along with eradication of HHV‐6 replication.…”
Section: Infection Of Erythroid Progenitorsmentioning
confidence: 99%